Literatura Afrofuturista: Identidade Negra Feminina nos Romances Kindred, de Octavia E. Butler e The Underground Railroad, de Colson Whitehead - Santos, Gisele Sousa (2024)
To discuss black identity in literature, more specifically in Afrofuturist literature, requires an exercise in considering history, society, and the publishing market. Afrofuturism was born as a classification for speculative fiction stories by black authors in the United States at the end of the 20th century, but it has grown into a much larger movement. Today it represents an entire struggle against the memoricide of black and African culture, through the fabrication of futures, presents and pasts that deal with the black presence in world History. Understanding and exploring Afrofuturism evokes reflection on unconventional approaches to time, history, and progress. From this perspective, we will dedicate our analysis to the protagonists of two contemporary Afrofuturist narratives that revisit episodes from the black population's past, Kindred (1979) by Octavia Butler and The Underground Railroad (2016) by Colson Whitehead. Our aim is to understand how black female identity is established in these characters, exploring the construction of this identity, and examining how the protagonists configure its aspects in their journeys.